Electrostimulation and physical training: a narrative review (Research, Society and Development, 2020)
Electrostimulation is a technique used by health professionals in treatments for various diseases and sports training. It can be applied in gyms, physiotherapy clinics and sports environments such as football clubs, races, among others. There are several nomenclatures on the market relating to electrical stimulation, but all of them are technically known as transcutaneous electrical neuromuscular stimulation (TENS). Full-body TENS is a relatively new technique, and has entered the market to enhance the treatment and training that were already used by local electrical stimulators, such as Russian, galvanic and other currents. The results of studies related to the theme differ widely, therefore, there is a need for more research related to the theme. Thus, the objective of this review is to identify and discuss the beneficial effects of TENS in the treatment of cardiovascular and neuromuscular diseases, including in the aid of conventional physical training and the potential risks to human health.